(untitled) (Global Journal of Human-Social Science, 2021)
The current coronavirus outbreak has made several organizations such as schools, churches, real estate consultants, tourist attraction centres begin to exploit the benefits of information technology to ensure the continuous running of their operation through website and television broadcast. The need for National Park in the developing countries to showcase their flora, fauna and environment through website and television broadcast intervention (WTBI) are not farfetched. It is believed WTBI could market and promote national parks in developing countries to potential tourists, because through website and television broadcast intervention WTBI, the developed countries have achieved high operational efficiency and income to increase National Park Visitation Intention (NPVI) of tourists. As such they have generated so much income through tourism to their national parks. The study utilized online survey to evaluate the adequacy of current WTB intervention puts in place by management of national parks in Nigeria and the consequent effects of improving on current WTBI to market and promote national parks in Nigeria.